RILU magazine. Organ of the Red International of Labour Unions. . Red International of Labour Unions monthly magazine
(1933) titled: Red International of Labour Unions monthly magazine. - Continues: The Red International of Labour Unions. Official organ ... (ZO 16009). - French ed.: L'Internationale syndicale rouge. Revue mensuelle ... (ZO 16007). - German ed.: Die Rote Gewerkschaftsinternationale (ZO 16006). - Russ.ed.: Krasnyj internacional profsojusov. Bjulleten' ... (ZO 16005). - Span.ed.: La Internacional sindical roja. Revista mensual ... (ZO 16008).